Age-related trends of physical activity and work capacity among men and women in an open urban population - A. M. Akimov (Российский кардиологический журнал)
Aim. To establish parameters of physical activity (PA) and work capacity among men and women in an open population of Western Siberia city, depending on age.Material and methods. Cross-sectional epidemiological studies were carried out among open male and female population of a middle-urbanized city of Western Siberia (Tyumen). Representative samples of 1000 people aged 25-64 years (250 people in each life decade) were analyzed. PA and work capacity were determined according to the WHO MONICA-psychosocial questionnaire “Awareness and Attitude towards Health”.Results. Age-related trends among young men of middle urbanized Western Siberia city were manifested by PA increase during the last year (in 25-34 yearage group — in 20,9%, in the general population — in 13,8% (p=0,0205)). During the last year, a decrease and an increase in work capacity was revealed in young women (33,6%) and young men (17,5%), respectively. Age-related trends among middle-aged people of both sexes were manifested by low self-esteem — in men by the sixth decade of life (0,6% vs 8,9%, p=0,0002), in women — by the fifth decade of life (3,4% vs 8,2%, p=0,0442). In men, with a decrease in PA and work capacity during the last year, an increase in outdoor activities was revealed (15,8% vs 27,7%, p=0,0020).Conclusion. Since the promotion of physical literacy should be among the state priorities, the presented data can serve as the basis for planning populationbased preventive measures, intended for working-age men and women in middleurbanized Siberian cities.